Research Information for Reasonable People - Dresser, Rebecca (The Hastings Center report, 2018)
In 2017, federal officials issued a revised version of the Common Rule, the federal regulations that govern much of the human subject research conducted in the United States. Two provisions on information disclosure have reportedly provoked confusion among researchers and people responsible for research oversight. These provisions incorporate the familiar and foundational legal concept known as the reasonable person standard, applying this to research disclosure. Although other, long-standing Common Rule provisions require reasonableness judgments, the new provisions differ in that they require reasonableness to be judged from the ordinary person's perspective instead of the perspective of scientists, clinicians, and other experts generally involved in designing and reviewing human studies.